Acquisition of Arabic Vocabulary Through the Book Al-‘Arabiyyah Baina Yadaik (I) in Foreign Language Course Institutions - Mitrajati, Kenyo; Zaini, Hisyam; Holilulloh, Andi (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study aims to describe the acquisition of Arabic through the book Al-'Arabiyyah Baina Yadaik (I) for course participants at the At-Tasniim Yogyakarta foreign language course institution. This research is qualitative with a case study approach. The research data is the Arabic language acquisition of the course participants. Sources of data obtained from course participants. Observation, interviews, and documentation carry out data collection techniques. While data analysis with data reduction, data presentation, and conclusion. The results of the study stated that the acquisition of Arabic vocabulary through the book Al-'Arabiyyah Baina Yadaik (I) at the foreign language course institute (LKBA) At-Tasniim Yogyakarta was passed by course participants in several phases; pre-production, early production, start-up, fluency, and finesse. Some Arabic vocabulary is taken from the book. More than 60% of course participants have succeeded in mastering Arabic vocabulary in the